KAJIAN PENGGUNAAN ASAP CAIR DAN GARAM TERHADAP BEBERAPA KOMPONEN MUTU DAN MASA SIMPAN IKAN KAKAP (Lutjanus sp) KERING - Chairul Anam A. Rahman (Faculty of Agricultural Technology, 2020)
This research was aimed to determine the combination of liquid-smoke and salt as natural preservatives to enhance the quality and shelf life of dried snapper fish (Lutjanus sp). The experiment was conducted using a complete randomized factorial design with sample combination on liquid smoke concentration respectively 0%; 2,5%; 5,0%; 7,5% and salt concentration of 0%; 2,5%; and 5,0%. Chemical and organoleptic data were analyed by analysis of variance at 5% significance level by using software Co-stat. A significant difference data were tested further by real difference test with honestly significant difference test, while the microbiological data were analyzed with a quantitative method. The results showed that the combination of liquid smoke and salt have not effect on the chemical properties of dried snapper fish (water content, salt content, and organoleptic quality on textur). However, the organoleptic quality on color, scent and flavor found to be affected; positive effect appeared after physical color test performed, i.e. L value and oHue. The sample treated with combination of 7,5% liquid smoke and 2,5% salt showed the best performance indicated by salt concentration and water content complied with standard based on SNI 01-2721-2009; color, scent, texture and flavor were acceptable based on organoleptic test; complied with food safety regulation on microbiology aspect, as indicated by value of total microbes up to 1,0 x 104 CFU/gram, total coliform up to 1,0 x 101 CFU/gram, and total fungus up to 1,0 x 102 CFU/gram. Therefore, it is recommended that combination of 7,5% liquid smoke and 2,5% salt is the best treatment to enhance the quality and safety of traditionally-processed dried snapper fish.